Experience Mode of Digital Media Art under Virtual Reality Technology - Xingming Wu; Yehan Li (Applied Bionics and Biomechanics)
With the progress of the country’s comprehensive strength and scientific strength, the development of science and technology has brought tremendous changes to people’s lives and at the same time brought information dissemination and media methods to a new stage. This article integrates VR technology into your digital media art experience. This combination not only reduces the distance between the experience and the art but also allows the experiencers to better understand what the artist wants to convey in the artwork. Virtual reality technologies and experts have shifted from bystanders to participants and experiencers. This is a brand new experience. It dispels our previous experience based on visual experience and forms a new form of experience. The final results of the study showed that the scores of the three classes of cognitive experience were 4.8, 4.6, and 4.7, with an average score of 4.7. With a full score of 5, the scores in the three dimensions are very high, indicating that this digital media art interactive experience design has brought students a good sensory experience, interactive experience, and cognitive experience.